Проблеми прогнозного визначення вартості будівництва - Жураковська, М. О. (Ways to Improve Construction Efficiency, 2013)
The mechanisms of reliable rating of building prices and volumes of capital investments to create building production are analyzed, the perspective usage of the special computer-aided technologies to forecast building value is proved.